Enterostomy Closure Timing for Minimizing Postoperative Complications in Premature Infants - Juyoung Lee; Min-Jung Kang; Han-Suk Kim; Seung-Han Shin; Hyun-Young Kim; Ee-Kyung Kim; Jung-Hwan Choi (Pediatrics and Neonatology)
For premature infants with advanced acute abdomen, creating a temporary enterostomy is believed to be an appropriate surgical management. However, there is no consensus regarding the timing of enterostomy reversal. The aim of this study was to determine the optimal timing for enterostomy closure (EC) by analyzing EC-related complications. Methods: This was a retrospective study of preterm infants who underwent enterostomy for suspected acute abdomens and subsequent closure. Results: EC-related complications occurred in 35 of 54 infants (65%). A univariate analysis determined the following risk factors for EC-related complications: lower weight and younger age at the time of EC and a shorter stoma duration. In a multiple logistic regression analysis, the only significant risk factor was a weight under 2660 g at the time of the closure operation. Infants with EC-related complications were ventilated longer, were administered more vasopressors, and were more likely to undergo reoperation. Additionally, these infants required parenteral nutrition for a longer duration, had a longer length of hospital stay after EC, and had a significantly lower weight and height at a corrected age of 7–10 months than infants without EC-related complications. Conclusion: Body weight may be one of the most important factors to consider for minimizing EC-related complications.